Carta de Bolívar Pagán a Roberto H. Todd - Pagán, Bolívar; Todd, Roberto H. (My University, 1924)
Carta de gastos de representación durante las elecciones.
Keywords: Partido Socialista Puertorriqueño.; Bazán, Antonio; Pagán, Bolívar